Estudio de factibilidad para la creación de una clínica veterinaria para la atención de perros y gatos por parte de la Fundación Gora Grupo operativo de rescate animal en la ciudad de Quito - Aguilar Pontón, María Yudely (2015)
The Feasibility Study for the creation of a veterinary clinic by the Gora Foundation in Quito, Kennedy sector is done in order to generate revenues to fund redemptions and maintenance of dogs and cats that roam the streets. The study was made in V chapters which are summarized below: Chapter I. Problem research and analysis of the objectives to determine what we will get with the implementation of the study. Chapter II. General and specific objectives of the study. Chapter III. Marco teórico que es la guía de los conceptos utilizados en cada uno de los capítulos. Chapter IV. Methodological framework type and method of research that will be done, techniques and data collection required is established. Chapter V. Proposal and results This chapter contains: market research that allows observing supply and demand in the market and which will host the new veterinary clinic; technical study observed the structure of veterinary clinic, equipment, materials and resources that will have to operate; financial study in which the initial investment required for the project to begin operations is detailed; and environmental and social assessment study. Finally, conclusions and recommendations of the study, all of which must be implemented, monitored and evaluated are presented.